2019
DOI: 10.1038/s41598-019-39992-8
|View full text |Cite|
|
Sign up to set email alerts
|

Intrinsic activation of cell growth and differentiation in ex vivo cultured human hair follicles by a transient endogenous production of ROS

Abstract: The emerging variety of signalling roles for ROS in eukaryotic cells and tissues is currently a matter of intense research. Here we make use of ex vivo cultured single human hair follicles as an experimental model to demonstrate that a transient production of non-lethal endogenous ROS levels in these mini-organs promotes efficiently the entry into the growth phase (anagen). The stimulatory process implicates the specific activation of the hair follicle stem cell niche, encompassing the induction of stem cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This may be important given recent insights into the role of peripheral clock activity in the control of murine and human HF cycling 47,48 . Within mitochondria, MPZL3 interacts with FDXR to promote ROS production, 13 a process shown to influence the HC, 49–52 as well as impact upon circadian clocks 53,54 . Moreover, since it is involved in mitochondrial electron transport and ROS production, 13 MPZL3 lies at the cross‐roads of HC control and HF mitochondrial energy metabolism, 17,19 making it a plausible candidate as a key regulatory molecule within the core HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important given recent insights into the role of peripheral clock activity in the control of murine and human HF cycling 47,48 . Within mitochondria, MPZL3 interacts with FDXR to promote ROS production, 13 a process shown to influence the HC, 49–52 as well as impact upon circadian clocks 53,54 . Moreover, since it is involved in mitochondrial electron transport and ROS production, 13 MPZL3 lies at the cross‐roads of HC control and HF mitochondrial energy metabolism, 17,19 making it a plausible candidate as a key regulatory molecule within the core HCC.…”
Section: Discussionmentioning
confidence: 99%
“…160 In line with this result, similar photoactivation treatment in ex vivo cultured human hair follicles cause anagen onset in a Wntdependent manner. 161 The discrepancy in these studies may suggest that long-term ROS has different effects from transient ROS or may be attributed to side effects from different ROS induction methods.…”
Section: Me Tabolis M a S A Cell-intrin S I C Mechanis M In Hfsc Smentioning
confidence: 97%
“…Although classically associated with oxidative stress, reactive oxygen species (ROS) at physiological levels play an important role in hair formation. Bulbar epithelial cells produce high amounts of ROS during hair growing 120 and studies using human ex vivo HFs organ cultures proved that transient endogenous ROS production promotes HF stem cell activation and anagen entry, which was associated with the activation of Wnt transcriptional factors 121 . Corroborating these observations, Hamanaka and coworkers 122 showed that mice genetically manipulated to prevent mitochondrial ROS generation in basal epithelium displayed impaired development of epidermis, HF and SG.…”
Section: Hair Follicle-related Signalingmentioning
confidence: 99%